Surabaya Students Reception of Cyberbullying on ‘One Word For Safno’ in @Jagungrebus8's Tiktok Account - Hanna Nurhaqiqi; Ni Made Indira Asmara Devi (International Journal of Social, Economic, and Business, 2025)
The purpose of this study is to analyze Surabaya students' responses to cyberbullying based on the “One Word for Safno” upload found on the TikTok account @Jagungrebus8. This research involved seven informants who were purposively selected from various universities in Surabaya. This qualitative approach uses Stuart Hall's reception theory. Data were collected through in-depth interviews and analyzed using thematic analysis to determine reception patterns based on three positions: dominant, negotiation, and opposition. The results showed that the dominant position was most prominent; students from psychology and law consistently believed that the content of “One Word for Safno” was a type of cyberbullying. Informants in this situation not only encountered systematic forms of cyberbullying but also experienced emotional effects such as discomfort, anger, and concern about the possibility of bullying becoming normalized on social media. They showed changes in their behavior, such as reporting harmful content more frequently and avoiding digital content. According to this study, Surabaya students showed high awareness of cyberbullying issues. In addition, the fact that female students are the most frequently experiencing online harassment, gives hope that the younger generation has the ability to be the change and build a more moral internet environment. The results have a significant impact on the process of building digital literacy programs that involve various disciplines, as well as regulations for moderation of social media platforms that are more responsive to cyberbullying issues.